Child Malnutrition and Family Food Security in the COVID-19 Pandemic - Iflan Nauval; Husnah Husnah; Marisa Marisa; Khairunnisa Khairunnisa; Linda Ayu Lestari; Nadya Irena Habib; Talitha Liony (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
At the beginning of 2020 the world was shocked by a disease that caused death with such easy transmission, namely through the respiratory tract. This disease is caused by a virus called corona. Corona virus is a new type of virus that has now shocked the world community. The problem is that this virus has managed to infect thousands of millions of people globally in a very short time, even humans who do not show symptoms of being infected with the corona virus can also spread it to other humans. In Indonesia itself, the total number of cases caused by the COVID-19 virus is increasing, so the government is trying to contain the spread of the COVID-19 virus. One of the ways that the government has taken to deal with the COVID-19 virus is by implementing large-scale social restrictions (PSBB). People's lives have changed since the implementation of Large-Scale Social Restrictions by the Government. These changes are felt in various fields of the economy, namely income, employment, expenditure and purchasing systems made by the community. As a result, many people cannot work and their income decreases, especially to meet food needs which can cause nutritional imbalances in the community. Expenditure and purchasing systems carried out by the community. As a result, many people cannot work and their income decreases, especially to meet food needs which can cause nutritional imbalances in the community. Expenditure and purchasing systems carried out by the community. As a result, many people cannot work and their income decreases, especially to meet food needs which can cause nutritional imbalances in the community.